2015
DOI: 10.1007/s10339-015-0647-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between spatial ability, visuospatial working memory and self-assessed spatial orientation ability: a study in older adults

Abstract: This paper describes some novel spatial tasks and questionnaires designed to assess spatial and orientation abilities. The new tasks and questionnaires were administered to a sample of 90 older adults (41 males, age range 57–90), along with some other tests of spatial ability (Minnesota Paper Form Board, Mental Rotations Test, and Embedded Figures Test) and tests of visuospatial working memory (Corsi’s Block Test and Visual Pattern Test). The internal reliability of the new tasks and questionnaires was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 50 publications
(64 reference statements)
4
52
0
2
Order By: Relevance
“…In the TD group the correlations between Floor Matrix task performance (in both the Map and Observation learning conditions) and the EASQ were negligible. This result supports the use of the Floor Matrix task in individuals with DS to capture aspects of their everyday navigation ability, such as outdoor movements to reach places (as previously suggested by Mitolo et al, 2015). The absence of any relation between Floor Matrix task performance and everyday life spatial activity in the TD group is plausible because 5 and 6 years old children (like those in our TD group) are not required or allowed to go around in the outside world alone (to go to school or visit other parts of their neighborhood).…”
Section: Discussion Of the Results And Conclusionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the TD group the correlations between Floor Matrix task performance (in both the Map and Observation learning conditions) and the EASQ were negligible. This result supports the use of the Floor Matrix task in individuals with DS to capture aspects of their everyday navigation ability, such as outdoor movements to reach places (as previously suggested by Mitolo et al, 2015). The absence of any relation between Floor Matrix task performance and everyday life spatial activity in the TD group is plausible because 5 and 6 years old children (like those in our TD group) are not required or allowed to go around in the outside world alone (to go to school or visit other parts of their neighborhood).…”
Section: Discussion Of the Results And Conclusionsupporting
confidence: 87%
“…Floor Matrix task (Adapted From Mitolo et al, 2015) This task assesses path learning from actual movements in a controlled vista space setting. It consists of a 4 × 4 matrix on the floor comprising 16 squares (of stiff cardboard) 50 × 50 cm in size, with a 10 cm gap between them, forming a whole square layout about covering 2.30 × 2.30 meters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the late nineties, it has been a critical tool to understanding how brain regions support navigation and unveiling the structural and functional neural correlates of spatial navigation [1][2][3][4]. VR tests of spatial cognition have proved more sensitive in identifying spatial navigation deficits in patient populations compared to more classic visuospatial 'pencil-and-paper' tests like the Mental Rotation Test [5]. For older patients, VR has the added advantage to be a less costly and safer alternative to real-world navigation tests, which are time and space consuming, as well as difficult to administer to a population sometime less able to walk [6].…”
Section: Introductionmentioning
confidence: 99%
“…Some associations are likely due to a common direct relation that a pair of variables has, for example, spatial ability and mental speed are affected by gender and both are associated. That being said, previous studies [48,49,50,51,52,53] indicated and discussed most of the associations.…”
Section: Discussion On Holzinger Resultsmentioning
confidence: 95%